Case report repairing orbital skin defects using composite flaps after giant eyelid-derived tumor excision and orbital exenteration. Issue 48 (December 2017) - Fan, Bin; Liu, Jian-Ju; Wang, Bei-Fen; Sun, Ying-Jian; Li, Guang-Yu
Abstract: Rationale: Though giant malignant tumors arising in the eyelid are rare, they often require extensive surgery for removal along with orbital exenteration. Because of this, repairing orbital defects is an important factor in the surgical strategy. Patient concerns: Case 1 was a 78-year-old nomad man who presented in the Department of Ophthalmology with a giant tumor in his right eyelid, which had developed over three years. Clinical examination revealed a huge pigmented, nonhealing ulcerated lesion, approximately 52×44×40 mm 3 in size. Case 2 was a 52-year old rural male complaining of a huge tumor in the right eyelid. Patient medical history revealed that the mass was initially the size of a soybean and gradually grew over 3 years to the size of a fist. Diagnoses: Histopathological examination of the tumors revealed that one was a basal cell carcinoma and the other a sebaceous gland carcinoma. Interventions: The two cases of giant malignant eyelid tumors were surgically excised using rapid frozen section margin control. Different pedicle myocutaneous flaps were used to repair the orbital skin defects. Outcomes: Postoperative follow-up showed perfect healing of the pedicle flaps and good patient compliance. The results of these cases indicate that covering exposed orbital cavities with composite pedicle mycuaneous flaps is a simple and practical strategy for orbital reconstruction. Not only does this help maintain orbital stability, but it also provides opportunities for patients to return to normal lives. Lessons: Although surgical management is often the first option for treatment of giant eyelid tumors, recurrence and mortality due to the tumors is still high after long-term follow-up. Therefore, early discovery and treatment is the best way to control the progression of giant eyelid tumors and enhance survivability.